Working from the Centre : Supporting Unit and Course Coordinators to Implement Academic Integrity Policies, Resources and Scholarship : Final Report. - Henderson, Fiona; Whitelaw, Paul A.; Jose, Penny (Office for Learning and Teaching, 2014)
This project builds on the ALTC work by Whitelaw and Henderson (2010) and the current academic integrity project led by Tracey Bretag, however it goes much further and acknowledges the critical role of unit/course coordinators and places them at the centre of effective teaching and learning. The project focused on the ways and means that course/ unit co-ordinators can be productively assisted in managing systems and harnessing teaching and learning resources to ensure that academic integrity policies are properly and comprehensively adhered to. The project did this by developing two databases on an open access website which will respectively address best practice for coordinators in interpreting and administering academic integrity policy as well as annotated teaching and learning activities and resources. The innovations include a feedback mechanism and a scholarship workshop. Each of these together will foster an improved learning experience for the students, better educational outcomes, an enhanced community of practice, professional development and improved scholarship.